Influenza epidemiology and influenza vaccine effectiveness during the 2016-2017 season in the Global Influenza Hospital Surveillance Network (GIHSN) - Baselga-Moreno, Víctor; Trushakova, Svetlana; McNeil, Shelly; Sominina, Anna; Nunes, Marta C; Draganescu, Anca; Unal, Serhat; Koul, Parvaiz; Kyncl, Jan; Zhang, Tao; Kuatbayeva, Ainagul; Ben-Salah, Afif; et al. (BMC public health, 2019)
BACKGROUND: The Global Influenza Hospital Surveillance Network (GIHSN) aims to determine the burden of severe influenza disease and Influenza Vaccine Effectiveness (IVE). This is a prospective, active surveillance and hospital-based epidemiological study to collect epidemiological data in the GIHSN. In the 2016-2017 influenza season, 15 sites in 14 countries participated in the GIHSN, although the analyses could not be performed in 2 sites. A common core protocol was used in order to make results comparable. Here we present the results of the GIHSN 2016-2017 influenza season. METHODS: A RT-PCR test was performed to all patients that accomplished the requirements detailed on a common core protocol. Patients admitted were included in the study after signing the informed consent, if they were residents, not institutionalised, not discharged in the previous 30 days from other hospitalisation with symptoms onset within the 7 days prior to admission. Patients 5 years old or more must also complied the Influenza-Like Illness definition. A test negative-design was implemented to perform IVE analysis. IVE was estimated using a logistic regression model, with the formula IVE = (1-aOR) × 100, where aOR is the adjusted Odds Ratio comparing cases and controls. RESULTS: Among 21,967 screened patients, 10,140 (46.16%) were included, as they accomplished the inclusion criteria, and tested, and therefore 11,827 (53.84%) patients were excluded. Around 60% of all patients included with laboratory results were recruited at 3 sites. The predominant strain was A(H3N2), detected in 63.6% of the cases (1840 patients), followed by B/Victoria, in 21.3% of the cases (618 patients). There were 2895 influenza positive patients (28.6% of the included patients). A(H1N1)pdm09 strain was mainly found in Mexico. IVE could only be performed in 6 sites separately. Overall IVE was 27.24 (95% CI 15.62-37.27. Vaccination seemed to confer better protection against influenza B and in people 2-4 years, or 85 years old or older. The aOR for hospitalized and testing positive for influenza was 3.02 (95% CI 1.59-5.76) comparing pregnant with non-pregnant women. CONCLUSIONS: Vaccination prevented around 1 in 4 hospitalisations with influenza. Sparse numbers didn't allow estimating IVE in all sites separately. Pregnancy was found a risk factor for influenza, having 3 times more risk of being admitted with influenza for pregnant women.
Keywords: senioři; Seasons; Influenza virus; senioři nad 80 let; těhotenství; Vaccine effectiveness; mladiství; vakcíny proti chřipce; Influenza, Human; Middle Aged; mužské pohlaví; Vaccination; Sentinel Surveillance; vakcinace; Adult; Influenza Vaccines; Adolescent; Influenza A Virus, H3N2 Subtype; dítě; virus chřipky A, podtyp H1N1; Child; Influenza A Virus, H1N1 Subtype; Aged, 80 and over; Child, Preschool; ženské pohlaví; Humans; předškolní dítě; Pregnancy; celosvětové zdraví; sentinelová surveillance; virus chřipky A, podtyp H3N2; lidé středního věku; Global Health; Surveillance; Hospitalization; hospitalizace; dospělí; Female; Aged; roční období; chřipka lidská; Epidemiology; lidé; Male